2019
DOI: 10.3389/fmicb.2019.00438
|View full text |Cite
|
Sign up to set email alerts
|

Dysbiosis of Skin Microbiota in Psoriatic Patients: Co-occurrence of Fungal and Bacterial Communities

Abstract: Psoriasis is a chronic inflammatory skin disease, whose pathogenesis involves dysregulated interplay among immune cells, keratinocytes and environmental triggers, including microbiota. Bacterial and fungal dysbiosis has been recently associated with several chronic immune-mediated diseases including psoriasis. In this comprehensive study, we investigated how different sampling sites and methods reflect the uncovered skin microbiota composition. After establishing the most suitable approach, we further examined… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

6
77
1
2

Year Published

2019
2019
2023
2023

Publication Types

Select...
6
3
1

Relationship

1
9

Authors

Journals

citations
Cited by 85 publications
(90 citation statements)
references
References 65 publications
6
77
1
2
Order By: Relevance
“…Using the software tool LEfSe [35], we discovered the genus Malassezia to be highly enriched in patients with an active RAS ulcer, which is consistent with the hypothesis of microbial shift in favor of opportunistic pathogens. This observation is also in line with published data connecting the presence of Malassezia with incidence of other diseases, including dandruff, seborrheic dermatitis, and psoriasis [36][37][38][39][40]. The second most abundant species in the Active RAS cohort was Candida albicans, often described either as a commensal or opportunistic pathogen in the oral cavity [34,41].…”
Section: Discussionsupporting
confidence: 88%
“…Using the software tool LEfSe [35], we discovered the genus Malassezia to be highly enriched in patients with an active RAS ulcer, which is consistent with the hypothesis of microbial shift in favor of opportunistic pathogens. This observation is also in line with published data connecting the presence of Malassezia with incidence of other diseases, including dandruff, seborrheic dermatitis, and psoriasis [36][37][38][39][40]. The second most abundant species in the Active RAS cohort was Candida albicans, often described either as a commensal or opportunistic pathogen in the oral cavity [34,41].…”
Section: Discussionsupporting
confidence: 88%
“…Balanced colonization of the normal skin microbiota contributes to inhibiting adhesion of pathogens, whereas imbalanced colonization of an abnormal skin microbiota can lead to skin diseases/disorders [ 4 , 5 , 6 ]. Previous studies have reported microorganisms on the skin that are beneficial [ 7 , 8 ] or detrimental [ 9 , 10 ] to the physiological activity of cells [ 1 , 11 ], and a variety of physiological alterations triggered in the skin can be explained based on this information [ 12 , 13 , 14 , 15 , 16 ]. Accordingly, alterations in microbial communities consisting of skin microbiota have been implicated in the diversification of skin physical or physiological properties and the occurrence of skin-associated diseases, such as acne [ 15 ], atopic dermatitis [ 14 ], psoriasis [ 12 ], and dandruff [ 13 ].…”
Section: Introductionmentioning
confidence: 99%
“…I-FABP has previously been used as a biomarker in patients with inflammatory bowel diseases [15], mesenteric ischemia [16], necrotizing enterocolitis [17], septic shock [18], acute pancreatitis [19] or acute decompensated heart failure [20]. Recently, increased I-FABP concentration has been confirmed in patients with psoriasis [10,21]. However, the association of I-FABP with the clinical course of psoriasis remains unexplored.…”
Section: Introductionmentioning
confidence: 99%